Revitalisasi Rintisan Desa Wisata: Menghidupkan Kembali Potensi Wisata Das Miring Sungai Krasak - Yuli Purwandari Kristianingrum; Siti Nurwulan Syahita (Direktorat Pengabdian kepada Masyarakat, 2023)
Universitas Gadjah Mada (UGM) Real Work Lecture (KKN) is a student service program to make a real contribution to society by applying the knowledge and skills they have. One of the problems faced is a decrease in the potential of tourism pilot areas due to the pandemic, namely the Das Miring tourism pilot in Kromodangsan, Lumbungrejo, Tempel. In order to overcome this problem, the UGM DPKM sent KKN PPM students to the area in the hope that they could find a solution and revive the Das Miring tourist destination armed with the knowledge they had gained during their studies. This research uses a qualitative method with a descriptive approach. The unit of analysis in this research is UGM KKN PPM Period 2 students in Kromodangsan, Lumbungrejo, Kapanewon Tempel, Sleman Regency. The data collection process was carried out through participatory observation and documentation. The results of this research show that the presence of students to carry out KKN in the area has made a significant contribution in developing the tourism potential of Das Miring. Students have made various efforts, including revitalization, development and promotion of the Das Miring tourist destination. In conclusion, this KKN program has succeeded in driving positive initiatives in supporting the recovery and development of neglected tourist destinations, proving the important role of students in providing concrete benefits to society.